آثار الصراع الدولي على النفط في جنوب السودان سياسياً واقتصادياً - صيوح لؤي; ديوب محمد; حسن نور (Latakia University Journal - Economic and Legal Sciences Series, 2019)
South Sudan occupies an important place in international strategic thinking due to the discovery of oil in it, which is one of the most important natural resources that major countries are struggling to obtain. South Sudan is a battleground between the United States of America, which followed the policy of imposing economic sanctions. the military solution at times, and at other times was to improve its relationship with South Sudan to serve its interests without taking into account the negative effects of its positions on the region, China, which played a dynamic role in the conflict on southern Sudan through its political, economic, On Israel, which sought to deepen conflicts in them to serve their strategic interests, as well as the positions of the African axis countries varied from southern Sudan according to the objectives and interests that seek to achieve. This led to the creation of a permanent political chaos in southern Sudan, leading to further political divisions, coalitions and attempts to overthrow the regime. Any attempt to build a unified political system in the region according to African and international standards, in addition to the deteriorating economic situation and impossibility Achieving consistency between economic, fiscal and monetary policies and the failure of the state to undertake development projects and improve the rate of growth to the required level. The State has also directed its support to the military sector as a result of the conflict. يحتل جنوب السودان مكانة هامة في الفكر الاستراتيجي الدولي، ويعود ذلك إلى اكتشاف النفط فيه، والذي يعد من اهم الموارد الطبيعية التي تتصارع الدول الكبرى للحصول عليها، فنجد أن جنوب السودان يعد منطقة تصارع بين الولايات المتحدة الامريكية التي اتبعت سياسة فرض العقوبات الاقتصادية، واباحة استخدام الحل العسكري تارة، وتارة أخرى كانت تبادر لتحسين علاقتها مع جنوب السودان بما يخدم مصالحها دون مراعاة الاثار السلبية لمواقفها على المنطقة، والصين التي لعبت دوراً ديناميكياً في الصراع على جنوب السودان عن طريق علاقاتها السياسية، والاقتصادية، والعسكرية، فضلاً عن إسرائيل التي سعت إلى تعميق الصراعات فيها بما يخدم مصالحها الاستراتيجية، كذلك تباينت مواقف دول المحور الافريقي من جنوب السودان بحسب أهدافها والمصالح التي تسعى لتحقيقها. كل هذا أدى إلى خلق حالة من الفوضى الدائمة على الصعيد السياسي في جنوب السودان، مما أفضى إلى مزيد من الانقسامات السياسية، والتحالفات، ومحاولات الانقلاب، والقضاء على أي محاولة لبناء نظام سياسي موحد في المنطقة وفق المعايير الافريقية والدولية، بالإضافة إلى الوضع الاقتصادي المتردي واستحالة تحقيق اتساق بين السياسات الاقتصادية المالية، والنقدية، وفشل الدولة في القيام بمشاريع تنموية وتحسين معدل النمو ليصل إلى المستوى المطلوب، بل قامت الدولة بتوجيه دعمها إلى القطاع العسكري نتيجة للصراع.